Impact of Extreme Drought Climate on Water Security of Machap Dam - Azahari, Muhammad Hafiz; Zahrem, Muhammad Ammar Danish; Zullazzamar, Siti Nuraisyah; Sahat, Suhaila (Multidisciplinary Applied Research and Innovation, 2023)
Due to climate change, severe changes throughout the rainy season and protracted dry seasons offer issues. Drought is harmful to human health and productivity. Extremely dry weather caused by severe drought can induce serious imbalances in water cycles, affecting rainfall patterns and evaporation, atmospheric water vapour circulation, and soil moisture content, resulting in decreased volumes in streams, rivers, and reservoirs. In September 2019, Johor began to feel the impacts of the extended heat and lack of rain. As a result, the water level at Machap Dam has reached critical levels. This study intends to calculate yearly rainfall intensities and identify year or month droughts that occurred between 2011 and 2020. The information was collected from the SPRHiN website. Rainfall per month, yearly rainfall, mean annual rainfall, variance, and percentage deviation were determined using completed rainfall data. The percentage deviation was used to identify extreme drought periods. According to the findings, the wettest year was 2018. The maximum precipitation happened in 2018, with a value of 2333.50 mm, while the lowest occurred in 2019, with a value of 1699 mm. The average rainfall throughout the ten years from 2011 to 2020 is 2050.373 mm. The findings reveal that the greatest annual rainfall happened in 2018, with a value of 2333.50mm, while the lowest annual rainfall occurred in 2019, with a value of 1699 mm. According to the findings, the average annual rainfall is 2050.373 mm. As a result, the study’s goal of determining annual rainfall intensities and year or month droughts was effectively accomplished. In future study, it is suggested that the data given be expanded so that it is easier to spot missing data.